Mechanistic insights into FUNDC2P4 and HSF1 regulation of EMT in residual hepatocellular carcinoma following insufficient radiofrequency ablation - Ni Tang (196698) (2025)
Insufficient radiofrequency ablation (IRFA) increases the risk of hepatocellular carcinoma (HCC) recurrence and metastasis. Our previous study revealed that IRFA downregulates FUNDC2P4 and promotes epithelial-mesenchymal transition (EMT), but the mechanisms remain unclear. We simulated IRFA in vitro using a thermostatic water bath and assessed RNA and protein expression via qRT-PCR and Western blotting. Transcriptome analysis of LV-FUNDC2P4-transfected Huh7 cells, along with computational prediction, truncated mutants, and dual-luciferase assays, was performed to investigate the competitive binding of FUNDC2P4 and heat shock factor 1 (HSF1) to the Chromobox protein homolog 7 (CBX7) promoter. Functional assays, including CCK-8, Transwell, and wound-healing assays, evaluated cell proliferation, invasion, and migration. IRFA induced EMT, downregulated FUNDC2P4, and upregulated HSF1. Gene set enrichment analysis indicated EMT suppression in Huh7 cells overexpressing FUNDC2P4. Overexpression of FUNDC2P4 increased CBX7 expression, while HSF1 overexpression reduced it. Co-transfection led to moderate CBX7 levels. Two overlapping binding sites within the CBX7 promoter were identified: the FUNDC2P4 triplex target site (nucleotides 1782–1832) and the HSF1 binding site (nucleotides 1790–1804). Functional studies suggest that FUNDC2P4 may compete with HSF1 to transcriptionally regulate CBX7, which in turn suppresses EMT and modulates HCC cell proliferation, invasion, and metastasis. These findings suggest a potential regulatory mechanism involving FUNDC2P4 and HSF1 that may contribute to HCC recurrence and metastasis after IRFA, warranting further in vivo and clinical investigation.